2020
DOI: 10.1530/joe-19-0239
|View full text |Cite
|
Sign up to set email alerts
|

Implication of glycogen synthase kinase 3 in diabetes-associated islet inflammation

Abstract: Islet inflammation is associated with defective β cell function and mass in type 2 diabetes (T2D). Glycogen synthase kinase 3 (GSK3) has been identified as an important regulator of inflammation in different diseased conditions. However, the role of GSK3 in islet inflammation in the context of diabetes remains unexplored. In this study, we investigated the direct implication of GSK3 in islet inflammation in vitro and tested the impact of GSK3 inhibition in vivo, on the reduction of islet inflammation, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 60 publications
1
20
2
Order By: Relevance
“…The mechanisms underlying the interactions between GSK3 and the GCs pathway have been investigated in several cell systems [ 22 , 23 , 43 , 45 ]. However, despite the central roles of both GSK3 [ 46 50 ] and GCs [ 15 , 17 , 19 , 51 ] in β-cell growth, survival and secretory function, their crosstalk in these cells has not been addressed. To the best of our knowledge, the present study is the first to uncover several aspects of the complex interplay between GSK3 and the GC pathway in β-cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying the interactions between GSK3 and the GCs pathway have been investigated in several cell systems [ 22 , 23 , 43 , 45 ]. However, despite the central roles of both GSK3 [ 46 50 ] and GCs [ 15 , 17 , 19 , 51 ] in β-cell growth, survival and secretory function, their crosstalk in these cells has not been addressed. To the best of our knowledge, the present study is the first to uncover several aspects of the complex interplay between GSK3 and the GC pathway in β-cells.…”
Section: Discussionmentioning
confidence: 99%
“…As an additional mechanism, GSK3β activity has been reported to be enhanced by GCs through the reduction of the phosphorylation of Ser9 residue of GSK3β [ 25 , 38 , 52 55 ], hence increasing its activity. Since GSK3 is a negative regulator of growth and survival in β-cells [ 46 50 ], we hypothesized that GCs pro-apoptotic effects could be mediated partly by the stimulation of GSK3 activity upon GC treatment. Here, we showed that GSK3 phosphorylation status was not affected by Dexa in INS-1 832/13 cells.…”
Section: Discussionmentioning
confidence: 99%
“…GSK3β is a serine/threonine protein kinase. GSK3β plays an important role in regulating cellular inflammatory response, nerve, glucose metabolism, heart, and reproductive function [1,12,15]. Inhibition to the activity of GSK3β reduced prostaglandin E2, serotonin, histamine, and other inflammatory 5 Mediators of Inflammation mediators in collagen II-induced rheumatoid arthritis in rats [30] and protected the nervous system from HIV-associated neurocognitive disorders [31].…”
Section: Discussionmentioning
confidence: 99%
“…Isoorientin reduces the hyperphosphorylation of the Tau protein and plays neuroprotective effects in SH-SY5Y cells [11]. Notably, GSK3 disorders are involved in a numbers of diseases, such as diabetes, reperfusion injury, mental stability, cancer, and neurodegenerative diseases [12][13][14][15], which are all related with inflammation. Sepsis leads to systemic inflammation and the destruction of homeostasis in the brain [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…As described in the next section, oxidative stress and mitochondrial alterations increase glucagon secretion at normal and high glucose and are therefore likely to accelerate the occurrence of frank hyperglycemia characteristic of diabetes. Hence, chronic infratherapeutic treatment of Goto-Kakizaki young rats with the GSK3 inhibitor, lithium, prevented islet inflammation and diabetes [82].…”
mentioning
confidence: 94%